Public private partnerships and co-production as drivers of effective social safety nets for rural women in Uganda - Barah, Chioma Ihuoma; Siambe, Omweri F.; Onsarigo, Thomas G.; Nyamboga, Tom Ongesa; Barah, Obinna Onyebuchi (Springer International Publishing, 2025)
Abstract This study examines the effectiveness of Social Safety Net Programs (SSNPs) in empowering rural women in Uganda’s Bushenyi District, focusing on the roles of public–private partnerships (PPPs), policy co-production, and skills enhancement. Using a convergent mixed-methods design, survey data from 124 women beneficiaries were integrated with qualitative insights from six key informant interviews and three focus group discussions. Regression analysis revealed that PPPs are a strong and significant predictor of SSNP effectiveness (β=0.418, p<.001), even after controlling for education (β=0.291, p<.01) and age (β=0.159, p<.05), explaining 59% of the variance in empowerment outcomes (Adjusted R² = 0.576). Qualitative findings showed that participatory design and context-responsive training, particularly in tailoring, agriculture, and financial literacy, enhanced women’s agency, economic independence, and access to services. Engaging African feminist and intersectional perspectives, the study highlights how PPPs and co-production can simultaneously reshape and, at times, reinforce existing power relations. The findings contribute to gender-responsive social protection scholarship by underscoring the need for governance and accountability mechanisms that move beyond transactional aid toward transformative gender equity. Practical recommendations emphasize embedding co-production, education-sensitive interventions, and skills development into SSNPs to advance the Sustainable Development Goals. Keywords Social safety net programs, Women’s empowerment, Collaborative governance, Policy co-production, Gender equity, Public-private partnerships (PPPs)
Keywords: Social safety net programs; Women’s empowerment; Collaborative governance; Policy co-production; Gender equity; Public-private partnerships (PPPs)